The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14095149
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Phase Alkylation of Isomeric Cresols with Tert-Butyl Alcohol over Perlite Supported Sulfated Zirconia Catalyst

Abstract: In the present study, perlite was thermally activated and then modified desirably to generate super acidity by loading different weight percentages of sulfated zirconia (SZ) via the two-step sol-gel method. As-prepared sulfated zirconia perlite (SZP) catalysts showed suitable catalytic potential in the vapor phase alkylation of o, m, and p-cresols with tert-butyl alcohol. The presence of crystalline phases in SZP catalysts was confirmed by XRD and FT-IR studies. TEM images revealed the nano size of the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Figure 7 shows the UV-Vis spectra of EP and PhEP (a), EP/PhBR and PhEP/PhBR composites (b), and PhBR (c). In the UV-Vis spectra of both EP and PhEP samples, peaks characteristic of aluminosilicates and explaining the presence of silica were observed at wavelengths of 254 nm and 243 nm, respectively [25]. As can be seen from Figure 7a, after the OxCh reaction of EP, the observed peak at 254 nm shifted to lower wavelengths (243 nm), and visible-light absorption improved.…”
Section: Uv-vis Spectroscopymentioning
confidence: 84%
“…Figure 7 shows the UV-Vis spectra of EP and PhEP (a), EP/PhBR and PhEP/PhBR composites (b), and PhBR (c). In the UV-Vis spectra of both EP and PhEP samples, peaks characteristic of aluminosilicates and explaining the presence of silica were observed at wavelengths of 254 nm and 243 nm, respectively [25]. As can be seen from Figure 7a, after the OxCh reaction of EP, the observed peak at 254 nm shifted to lower wavelengths (243 nm), and visible-light absorption improved.…”
Section: Uv-vis Spectroscopymentioning
confidence: 84%
“…The % selectivity of 2-TBC increased when the molar ratio increased from 1 to 2, and this increase became negligible afterwards. The % selectivity of 2,6-DTBC increased when increasing the concentration of tert-butyl alcohol due to the greater resident time of the mono tert-butylated product on the catalyst surface [33]. As the conversion of p-cresol and the selectivity toward 2-TBC are higher at a molar ratio of p-cresol to tertiary butanol of 1:2, the optimum molar ratio was fixed at 1:2.…”
Section: Effect Of Molar Ratio Of Tert-butyl Alcohol To P-cresolsmentioning
confidence: 99%
“…Sarish et al studied the alkylation of p-cresol with tertbutanol over WOx/ZrO 2 catalysts and the corresponding catalytic activity, which was compared with sulfated zirconia and zeolites like USY, H, and montmorillonite K-10, under optimized reaction conditions and concluded that the activity of sulfated zirconia was lower than that of the WO 3 /ZrO 2 catalyst [32]. Malpani et al designed a perlite-supported sulfated zirconia catalyst for the alkylation of isomeric cresols with tert-butyl alcohol, and the study revealed better conversion with few limitations [33].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Heterogeneous solid acids comprising diverse materials have been reported in the recent past for the production of tert-butylate m-cresol. Materials based on sulphated zirconia, 16 Al-MCM-41 molecular sieves, 17 Supported 12-tungstophosphoricacid and 12-tungstosilicicacid, 18 Perlite Supported Sulfated Zirconia, 19 12-tungstophosphoricacid and 12-tungstosilicicacid supported onto neutral alumina 20 are reported in the literature.…”
mentioning
confidence: 99%